ROLE OF PROTECTION PROVIDED BY EMBLICA OFFICINALIS LINN. AGAINST RADIATION AND LEAD INDUCED HISTOLOGICAL CHANGES IN THE JEJUNUM OF SWISS ALBINO MICE - Purohit, *R.K.; Chakrawarti, Aruna; Agarwal, Manisha; Jangir, Ashok; Ram, Purkha; Lal, Pyare; Nayak, Kamal kumar (International Journal of Ayurveda and Pharma Research, 2015)
Exposure to ionizing radiation increases the production of the reactive oxygen species (ROS) leading the irradiated cells into a state of oxidative stress. Furthermore, Lead exposure along with ionizing radiation can potentially become toxic to the tissues due to the heightened oxidative stress. In the present study adult male Swiss albino mice were procured and divided into seven groups. Group (II to IV) serving as control, received sub lethal dose (3.0 Gy or 6.0Gy) and /or lead acetate (20ppm) in drinking water ad libitum. The experimental groups (V to VII) were given aqueous solution of Emblica (1000 mg/ Kg b.wt./ animal/ day) orally seven days prior to radiation and/or lead acetate treatment. Sham- irradiated animals of Group I served as normal. Animals of all the groups were autopsied at each post treatment interval of 1, 2, 4, 7, 14 and 28 days. After the experiments observed number of lesions in the intestinal epithelium from outer coat to inner mucosa. Loosened sub mucosa with hyperaemia and hemorrhage, shortened crypts and a number of apoptotic cells with severe cytoplasmic variations were noted. Villi had a rough surface, wavy epithelium and hydropic degeneration up to day-2 and thereafter, a recovery from intestinal lesions was initiated and noticed till the last autopsy interval. After the combined exposure of gamma radiation and lead acetate, Group IV exhibited same pattern of damage but severe histopathological alteration than individual exposure of radiation or lead acetate indicating “synergistic “effect. Process of recovery started on day-14 after the combined treatment but the process was slow. The Combined treatment showed synergistic effect. In experimental groups less severe radiolesions and an early onset of recovery was observed. Therefore it may be deduced that Emblica is a good herbal radioprotector and may be useful for the clinical applications in human beings during radiotherapy.